English newspaper coverage of financial education on old age savings - Ng, Chooi Fun (2018)
Malaysia is projected to become an aged nation by 2030 and Malaysians are projected to live longer. Past research posit that individuals were not saving enough for retirement. Thus, adult Malaysians need to save more for their old age. This study examined how Financial Education (“FE”) on Old Age Savings (“OAS”), if any, was disseminated by a local English newspaper based on the following four objectives – describe the FE on OAS Themes covered by the Malaysian newspapers; explore the FE on OAS Providers; explore the FE on OAS Article’s Target Audiences; and explore the Presentation of FE on OAS Articles. This study used the qualitative research in the examination (“document analysis”) of the newspaper articles. A data template was constructed to capture the relevant fields and sub-fields that was required for data analysis. The FE on OAS Providers, Target Audiences and Narrative Visualizations were explored using content analysis. While, the description of the FE on OAS Themes, what financial goals were included and the tonality used in the FE on OAS articles were explored using thematic analysis. The FE on OAS Articles did not follow a standard curriculum but were based on current issues emphasizing mainly on Savings. It was found that key stakeholders of the proposed National Financial Literacy Programs were not included as content providers and information provided did not include all financial products and services. Lastly, most of the FE on OAS Articles were targeting the employees and those with EPF savings. Through this study, the findings could be used (1) as input to enhance policy making decisions in terms of setting, adopting and implementing a standardized FE Curriculum for adult Malaysians, (2) as a basis to improve the cooperation between various stakeholders and FE on OAS Providers, (3) to support the financial education initiatives to include all segments of adult Malaysians facing different financial circumstance and preparing for different life goals and finally (4) to increase awareness on the need to expand the current initiatives undertaken by Malaysian newspapers to include all relevant FE on OAS Themes, FE on OAS Providers, all segment of population using various methods of presenting the contents in the articles. A standardized FE curriculum is recommended to be adopted and disseminated by all stakeholders and FE on OAS Providers to all segments of adult Malaysians. These initiatives would enhance their awareness and assist them to save more for their old age.